1995
DOI: 10.1002/ajmg.1320580110
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma in a boy with MCA/MR syndrome, deletion 11q, and duplication 12q

Abstract: Deletion 11q23-->qter and duplication 12q23-->qter are described in a boy with neuroblastoma, multiple congenital anomalies, and mental retardation. The patient has clinical manifestations of 11q deletion and 12q duplication syndromes. The possible involvement of the segment 11q23-->24 in the cause of the neuroblastoma is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Evidence for its particular role in tumor development has come not only from the frequency of this aberration in primary tumors (26% in the present study) but also because constitutional 11q alterations were reported in neuroblastoma patients (16,17). Nonconstitutional rearrangements affecting chromosome 11 often lead to the formation of a derivative chromosome 11 through unbalanced translocation with chromosome 17 as the main partner (18 -21).…”
Section: Discussionmentioning
confidence: 59%
“…Evidence for its particular role in tumor development has come not only from the frequency of this aberration in primary tumors (26% in the present study) but also because constitutional 11q alterations were reported in neuroblastoma patients (16,17). Nonconstitutional rearrangements affecting chromosome 11 often lead to the formation of a derivative chromosome 11 through unbalanced translocation with chromosome 17 as the main partner (18 -21).…”
Section: Discussionmentioning
confidence: 59%
“…To our knowledge, this is the first case of a 12q22q24.33 pure duplication. In a review of nine cases with wider 12q duplications, Koiffmann et al [1995] emphasized the similarity of the physical findings among the reported individuals, suggesting a clinically distinct syndrome. In order to contribute to a better karyotype/phenotype correlation, in this review we considered only four cases of 12q pure duplication involving a chromosomal region partially overlapping those identified in present case (Table I).…”
Section: Discussionmentioning
confidence: 96%
“…Deletions of 11q have been noted in approximately 15 ± 20% of reported neuroblastoma karyotypes (Mertens et al, 1997), and transfer of an intact chromosome 11 into the neuroblastoma cell line NGP induced dierentiation (Bader et al, 1991). Constitutional rearrangements of 11q have also been observed in some neuroblastoma patients (Bown et al, 1993;Koimann et al, 1995;Moorhead and Evans, 1980;Pegelow et al, 1975), suggesting that disruption of an 11q gene may predispose to the development of neuroblastoma. Loss of heterozygosity (LOH) for 11q was detected in 5 ± 32% of primary neuroblastomas using restriction fragment length polymorphism markers (Fong et al, 1992;Srivatsan et al, 1993;Takeda et al, 1996;Takita et al, 1995).…”
Section: Introductionmentioning
confidence: 99%